Differences in wayfinding performance across types of navigation aids and understanding of environmental information among travelers - Hung-Yu Chen; Kiminobu Sato; Meng-Cong Zheng (Journal of Asian Architecture and Building Engineering, 2021)
This study investigated the wayfinding strategy and efficiency. Experiments involving 44 participants (22 Japanese and 22 Taiwanese nationals) were conducted in Tamsui, Taiwan and Yokohama, Japan. Experimental tools included electronic and paper maps. Participants were in an unfamiliar environment, understood environmental information differently, and used different navigation tools. The researchers recorded the participants’ walking time, path, and the number of turns from the starting point to the destination. SPSS statistical software was used to conduct one-way and two-way analysis of variance (ANOVA). The findings revealed the following. First, when navigating linear roads and being uncertain about the accessibility of map-presented roads, relative to local participants, foreign participants were more likely to choose roads that were at the exit of the MRT station and take more identifiable roads. Second, all participants used landmarks when navigating intersecting parallel roads, but participants who used paper maps were more likely to use obvious buildings as landmarks. Third, in the wayfinding process, participants who used both electronic and paper maps made more turns when wayfinding in a familiar environment than in an unfamiliar environment. Participants familiar with the navigation tool exhibited a lower walking time.